PENDEKATAN MULTIDISIPLIN TERHADAP KONSEP HUDA DALAM AL-QUR’AN: SOLUSI UNTUK TANTANGAN KONTEMPORER - Aji Swasono, Pangestu; Miftakhussurur, Miftakhussurur (Institut PTIQ Jakarta, 2024)
This study aims to explore the epistemological dimension of huda in the Qur'an as a framework relevant to addressing global challenges such as inclusive education, social sustainability, and economic justice. This research employs a qualitative approach using the library research method, analyzing primary and secondary sources related to the concept of huda. The study seeks to uncover the potential of huda as a set of universal values applicable in modern contexts. The research background highlights the dominance of normative approaches in Islamic studies, which often overlook the relevance of social contexts and global challenges, thus limiting innovation in Islamic intellectual discourse. The results indicate that huda holds great potential to be developed into practical guidelines, especially through multidisciplinary integration such as technology and education rooted in Islamic values. However, the study also identifies obstacles, including a lack of interdisciplinary collaboration and resistance to innovation in Islamic studies. The novelty of this research lies in identifying a significant gap in the exploration of the epistemological dimension of huda, which has been largely underexamined in Islamic discourse, and emphasizing the need for a paradigm shift from normative to more progressive approaches. This study contributes conceptually to developing Qur'anic interpretations that are more relevant to contemporary challenges and applicable in addressing global needs.